IMPLEMENTASI SOFWARE AS A SERVICE PADA SISTEM E-ZAKAT - Fatihana, T Mohammad Bakti (Majalah Ilmiah UNIKOM, 2020)
Zakat is a compulsory worship for every Muslim. At present there are still many zakat institutions that are still manually in archiving data. With the existence of a web-based system needed to facilitate the process of delivering information and efficient communication in terms of cost and operation. Cloud computing is a technology that can expand network access and reduce costs because cloud networks operate at higher efficiency and with greater utilization, significant cost reductions are often encountered. This study discusses the application of software as a service to the zakat system which focuses on the receipt and distribution of zakat. The object is used by observing in zakat institutions. The results showed that the e-zakat system that was created could help the zakat institutions in making the receipt and distribution of zakat. Key Words: Cloud computing, Zakat, Zakat Institutions